A new approach to identifying the potentialities of User Experience techniques - Silva Júnior, João Batista da; Kronbauer, Artur Henrique (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2018: Proceedings of the 24th Brazilian Symposium on Multimedia and the Web, 2018)
Nowadays, there are a lot of techniques to evaluate the hedonic experiences of users with the use of technological products. The main problem is that, the fact that these techniques use different denominations for each type of feeling they can collect, make hard for evaluators to identify what exactly each technique can evaluate. Moreover, it is important to know the potential of each feeling, so the evaluators can choose the most appropriate technique for each type of evaluation. looking on that way, this article presents a new approach to identify the feelings that each User eXperience (UX) technique manages to encompass and what its potentialities are. The results of the study are promising, having as a legacy the description of the approach and the results of the evaluation of five UX techniques based on a self-report questionnaire.